The future of the biblical past : envisioning biblical studies on a global key - Boer, Roland, 1961-; Segovia, Fernando F. (Semeia studies, 2012)
"What does global biblical studies look like in the early decades of the twenty-first century, and what new directions may be discerned? Profound shifts have taken place over the last few decades as voices from the majority of the globe have begun and continue to reshape and relativize biblical studies. With contributors from Africa, Asia, the Pacific, Europe, Latin America, the Caribbean, and North America, this volume is a truly global work, offering surveys and assessments of the current situation and suggestions for the future of biblical criticism in all corners of the world."--Back cover